2007
DOI: 10.1364/josaa.24.003198
|View full text |Cite
|
Sign up to set email alerts
|

Inferring path average C^2_n values in the marine environment

Abstract: Current mathematical scintillation theory describing laser propagation through the atmosphere has been developed for terrestrial environments. Scintillation expressions valid in all regimes of optical turbulence for propagation in the maritime environment, based on what we believe to be a newly developed marine atmospheric spectrum, have been developed for spherical waves. Path average values of the structure parameter, C(n)(2), were inferred from optical scintillation measurements of a diverged laser beam pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Several experimental data and measurements indicate that the turbulence in the upper troposphere and stratosphere, or along nonhomogeneous path, deviates from predictions of the Kolmogorov model [2][3][4][5][6]. Other experiments showed that atmospheric turbulence in maritime environments can assume a different statistical behavior with respect to Kolmogorov [7][8][9][10][11][12][13]. In addition, anisotropy in stratospheric turbulent inhomogeneities has been experimentally investigated [14][15][16][17], and laboratory results have shown that turbulence can be anisotropic.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental data and measurements indicate that the turbulence in the upper troposphere and stratosphere, or along nonhomogeneous path, deviates from predictions of the Kolmogorov model [2][3][4][5][6]. Other experiments showed that atmospheric turbulence in maritime environments can assume a different statistical behavior with respect to Kolmogorov [7][8][9][10][11][12][13]. In addition, anisotropy in stratospheric turbulent inhomogeneities has been experimentally investigated [14][15][16][17], and laboratory results have shown that turbulence can be anisotropic.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional Kolmogorov spectrum is primarily used in theoretical studies due to its simplicity but is valid only in the inertial subrange. Recently the marine atmospheric refractivity spectrum that presents a multiplicative factor able to describe the aforementioned characteristic bump was proposed and takes the form [12] …”
Section: Marine Atmospheric Refractivity Spectral Modelmentioning
confidence: 99%
“…The effects of humidity over water make the optical waves' propagation more complicated [9,10], and the interaction between the humidity and temperature fluctuations in the marine atmosphere needs to be considered. Based on experimental data taken over the Salton Sea [10], recently a new analytic marine atmospheric refractivity spectrum has been developed [11,12], and it revealed a significant amplification of the characteristic bump compared with the terrestrial refractivity spectrum. The pronounced bump in the refractivity spectrum derived from the Salton Sea data is believed to generally represent the marine atmosphere [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the effect of the inner-scale of turbulence, researchers [3] developed the irradiance fluctuation expressions of plane and spherical waves on the basis of the new maritime spectrum in weak optical turbulence. In maritime environments, Vetelino et al [4] proposed theoretical scintillation expressions under moderate-to-strong Kolmogorov turbulence. In weak non-Kolmogorov maritime atmospheric turbulence channels, scintillation and aperture averaging of Gaussian beams were investigated [5].…”
Section: Introductionmentioning
confidence: 99%